THE USAGE OF INFORMATION RETRIEVAL TOOLS: DIFFERENCES BETWEEN LITHUANIAN AND PORTUGUESE STUDENTS - Jakutienė, Rita; Civilkienė, Daiva (PROFESSIONAL STUDIES: Theory And Practice, 2022)
With the development of information technologies, more and more information retrieval tools, containing a wide variety of information, can be found. Internet resources, universal and specialized search engines, virtual libraries are becoming the main information retrieval tools for students. The article introduces an exploratory (pilot) research aiming to find out the differences of information retrieval between Lithuanian and Portuguese students. Šiauliai State College offers a unique study programme Information Management, having a signed contract of a double diploma with Porto (Portugal) Polytechnic Institute Porto Accounting and Business School (ISCAP). 10 Portuguese and 10 Lithuanian students participated in the research. The online questionnaire was forwarded to the students of ISCAP Porto Accounting and Business School and to the second year students of the study programme of Information Management at Šiauliai State College. The research revealed that the respondents Lithuanian students look for scientific papers and books, whereas Portuguese students search for basic information and scientific papers. All the respondents of the survey identified Google Scholar as the most important search engine for scientific information retrieval. Key words: information retrieval, information retrieval tools, information retrieval systems, Portuguese students, Lithuanian students.